Corporate risk management for international business - Kucuk Yilmaz, Ayse; Flouris, Triant G. (Springer, 2017)
This book presents research on how businesses can be empowered to manage their company's risk exposure in international settings. It elaborates on approaches that advocate the minimizing of threats and sizing opportunities as the best strategy through which corporate objectives are maximized. With a focus on international business management, the book starts off with a review of literature and companies that are international in nature, before presenting several main chapters that highlight the different vital sides of both international business and risk management. Corporate Risk Management for International Business serves as a key source for managers and academic researchers in risk management and strategy to understand all related issues of managing risks and setting strategies in global way. The book also serves as a decision making guide for managers that are active in volatile and dynamic environments of international business.
Keywords: Risk management.; International business enterprises -- Management.; elektronické knihy; electronic books